A model for e-learning systems quality assessment with emphasis in Pakistan / Shahid Farid - Shahid, Farid (2016)
E-learning systems have been implemented widely in Higher Education Institutions (HEIs) round the globe. The poor quality of e-learning systems is one of the major causes of number of reported failures. Researchers have proposed quality models of the e-learning systems but most of them have focused on pedagogical perspective only. A very limited attention is given to assess the quality of e-learning systems from software perspective. Hence, it is quite difficult to measure the overall quality of an e-learning system in an effective manner. In this study, a pragmatic mixed mode methodology has been adopted to overcome the challenge of the quality assessment of e-learning systems. An exploratory study has been conducted to identify and prioritize the critical challenges of e-learning implementation according to their criticality and importance. Systematic Literature Review (SLR) has been conducted to probe the research focus formulated in our exploratory study. An exhaustive list of forty-two quality characteristics which make the foundation for the proposition of a Sustainable Quality Assessment Model for E-Learning Systems (SQAMELS) has been developed. Moreover, process guidelines for the utilization of the SQAMELS have also been formulated. The SQAMELS encompasses of three major dimensions namely system quality, service quality and charisma. The proposed solution contributes in a fashion to be utilized by the HEIs of developing countries like Pakistan for the quality assessment of their e-learning systems. Moreover, this study facilitates the researchers and academicians by providing recommendations for future research regarding the assessment and evaluation of the quality of the e-learning systems. The developed model and the approach has been evaluated by a) comparative analysis of features with existing e-learning quality models and frameworks, b) survey analysis by practitioners to measure the applicability c) experts review to gauge its usefulness and d) conducting a case study to assess the applicability and utility of the proposed model. The results showed that there is no significant difference amongst the experts and practitioners at the 95% confidence level. This indicates that the SQAMELS is applicable and useful for the quality assessment of the e-learning system for the HEIs of developing countries such as Pakistan.